Piezoelectric Nanowire toward Harvesting Energy from In-Vivo Environment - Ali Ghareaghaji (Bulletin of Electrical Engineering and Informatics, 2015)
This paper discusses technologies used to harvest energies from in-vivo environment. The discussion mainly concentrated on  nanogenerators based on Piezoelectric nanowires which are employed for converting biomechanical energy (such as muscle stretching), vibration energy (such as heart rate sound, sound waves) and  biohydraulic energy (such as blood flow, contraction of blood vessel) into electric energy. At the end this paper studies an approach for harvesting biomechanical and biochemical energies from living organisms simultaneously. This system, by using aligned nanowire arrays, can power medical nanosystems and nanodevices through converting vibration, biomechanical and biohydrulic energies into electricity. On the other hand by using biofuel cell structure, this hybrid cell can convert biochemical (glucose/O2) energy in biofluid into electricity. This technology can provide adequate power required for feeding nanodevices and nanosystems or at least to indirectly charge battery of the device. This technology can provide a sound basis for designing wireless self-powered nanodevices with direct energy harvesting from in-vivo environment.